Determination and fixation of natural water sources in Chile : The limit between a national asset for public use and the private property - Cabrera Pacheco, Alejandra (Derecho Público Iberoamericano, 2018)
In this paper, we determinate the legal rules governing our country in natural channels as national assets for public use in terms of their relationship with riparian properties. We will analyze how the jurisprudence and administrative bodies have faced and solved conflicts that arise in between the two types of property, specifying if these solutions have been correct. We finish with the relevant conclusions